(untitled) (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2017)
Conditions that occur in the calculation of land tax and building in the Cileunyi District Office already using is based on Law No. 12 of 1994, but in performing procedures tax such as making tax monthly and annual reports are still using Microsoft Office Excel 2007. To the problems, then writer take the title: "Perancangan Sistem Informasi Akuntansi Pajak Bumi dan Bangunan (PBB) Pada Kantor Kecamatan Cileunyi Bandung Dengan Menggunakan Microsoft Visual Basic 6.0 Dan Microsoft SQL Server 2000 Berbasis Client Server". The research used is basic research, the data used is qualitative data and quantitative data, the type of research design used is research design with primary data and secondary data, method of research used is exploratory research and descriptive, data collection techniques used is research field that consists of an interview and observation and research library.